71‐1: Large‐area Optical Fingerprint Sensors for Next Generation Smartphones. Issue 1 (29th May 2019) - Akkerman, Hylke; Peeters, Bart; Tordera, Daniel; van Breemen, Albert; Shanmugam, Santhosh; Malinowski, Paweł; Maas, Joris; de Riet, Joris; Verbeek, Roy; Bel, Thijs; de Haas, Gerard; Hermes, Dorothee; et al.
Abstract : We present large‐area photodetector arrays in combination with a thin‐film optical collimator for under‐display fingerprint authentication in next‐generation smartphones. The fabrication is compatible with flat panel display processes and based on an oxide TFT backplane with a printed organic photodiode frontplane. The functionality behind an AMOLED display is demonstrated.